Effect of a multicomponent behavioural PMTCT cluster randomised controlled trial on HIV stigma reduction among perinatal HIV positive women in Mpumalanga province, South Africa - Karl Peltzer; Suat Babayigit; Violeta J. Rodriguez; Jenny Jean; Sibusiso Sifunda; Deborah L. Jones (Taylor & Francis Group, 2018)
Background: We evaluate the impact a multicomponent, behavioural, prevention of mother to child transmission (PMTCT), cluster randomised controlled trial on HIV stigma reduction among perinatal HIV infected women in rural South Africa. Methods: In a cluster randomised controlled trial, twelve community health centres (CHCs) in Mpumalanga Province, South Africa, were randomised; pregnant women living with HIV enrolled received either: A Standard Care (SC) condition plus time-equivalent attention-control on disease prevention (SC; 6 CHCs; n =357), or an Enhanced Intervention (EI) condition of SC PMTCT plus the 'Protect Your Family' intervention (EI; 6 CHCs; n =342). HIV-infected pregnant women in the SC attended four antenatal and two postnatal video sessions; those in the EI, four antenatal and two postnatal group PMTCT sessions, including stigma reduction, led by trained lay health workers. Maternal PMTCT, HIV knowledge and HIV related stigma were assessed. The impact of the EI was ascertained on stigma reduction (baseline, 12 months postnatally). A series of logistic regression and latent growth curve models were developed to test the impact of the intervention. Results: In all, 699 women living with HIV were recruited during pregnancy (8-24 weeks), and assessments were completed prenatally at baseline and at 12 months (59.5%) postnatally. Baseline scores of overall HIV related stigma and the four scale factors (personalised stigma, disclosure concerns, negative self-image, and concern public attitudes) decreased at follow-up in the intervention group, while baseline scores of overall stigma and three scale factors (personalised stigma, negative self-image, and concern public attitudes) increased at follow-up in the control group. Using longitudinal analyses, Model 1, which included time-invariant predictors of stigma assessed over the two time periods of baseline and 12 months, increases in stigma from baseline to 12 months were associated with being unemployed, having been diagnosed with HIV before the current pregnancy, and alcohol use. In Model 2, which included time-varying predictors, lower stigma scores were associated with participation in the intervention, greater male partner involvement, and consistent condom use. Conclusion: The enhanced PMTCT intervention, including stigma reduction, administered by trained lay health workers had a significant effect on the reduction of HIV related stigma. Trial registration: clinicaltrials.gov: number NCT02085356